2019
DOI: 10.1016/j.ejvs.2019.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler 24 Hours after Carotid Endarterectomy Accurately Identifies Patients Not at Risk of Cerebral Hyperperfusion Syndrome

Abstract: WHAT THIS PAPER ADDSA validated prediction model for prevention of cerebral hyperperfusion syndrome (CHS) following carotid endarterectomy (CEA) is lacking; however, early recognition of cerebral hyperperfusion (CH) is crucial to prevent this complication. Intra-operative transcranial Doppler (TCD) is the gold standard to predict the risk of CH in CEA patients under general anaesthesia, but this study finds that post-operative TCD 24 h after CEA is more effective at predicting CH and CHS and is excellent at id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…systolic BP ≤140 mmHg). 14,23,24 As a consequence, a standard 160 mmHg maximum BP policy will still allow for severe complications of CHS to occur despite following a BP policy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…systolic BP ≤140 mmHg). 14,23,24 As a consequence, a standard 160 mmHg maximum BP policy will still allow for severe complications of CHS to occur despite following a BP policy.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, only a small subset of patients requires strict and immediate BP lowering and monitoring on a HCU while the majority of operated patients can safely be discharged for further BP regulation via the nursing ward or via the outpatient clinic. 14,25 This risk based strategy will lead to a decrease in hospital costs and is more patient-friendly than standard extended strict BP monitoring by a radial artery line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an actual clinical setting, there is concern about hyperperfusion. For example, post‐carotid endarterectomy prolonging cerebral hyperperfusion could potentially result in adverse events such as headache, edema, and even intracerebral hemorrhage [36]. However, the hyperperfusion after endarterectomy is caused by the structural change of the carotid artery, which is long‐term.…”
Section: Discussionmentioning
confidence: 99%
“…33 Studies showed that postoperative cerebral blood flow velocity increased by more than 100% compared with that before surgery, suggesting cerebral hyperperfusion syndrome. 34 We can also use postoperative CTP imaging to observe cerebral blood flow (CBF), cerebral blood volume (CBV), and mean transit time (MTT) to identify END. 33,35 In short, postoperative serum biomarker (occludin) combined with cranial imaging (CT/CTP/ TCD) could significantly improve the detection rate of END, which will have important guiding value for clinicians.…”
Section: F I G U R E 1 Serum Occludin Levels In Different Subgroups (A)mentioning
confidence: 99%